1961
DOI: 10.5928/kaiyou1942.17.141
|View full text |Cite
|
Sign up to set email alerts
|

On the Variations of the Daily Mean Sea Levels along the Japanese Islands

Abstract: The variations of the daily mean sea levels at 22 tide stations along the Japanese coast and their relations to the oceanographic and meteorological phenomena were examined. It was found that the variations are closely related to the oceanographic conditions,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

1968
1968
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 2 publications
0
11
1
Order By: Relevance
“…Abnormal high tides induced by such mechanisms have been investigated on various coasts across the world. For instance, Shoji [31] demonstrated, using the data from 22 tidal stations in Japan, that the daily mean sea levels move along the coast. Such traveling means waters could be separated into two types of waves, namely internal Kelvin-type waves and continental shelf waves [32].…”
Section: Yearly Rate Of Water Level Rise and Land Subsidencementioning
confidence: 99%
“…Abnormal high tides induced by such mechanisms have been investigated on various coasts across the world. For instance, Shoji [31] demonstrated, using the data from 22 tidal stations in Japan, that the daily mean sea levels move along the coast. Such traveling means waters could be separated into two types of waves, namely internal Kelvin-type waves and continental shelf waves [32].…”
Section: Yearly Rate Of Water Level Rise and Land Subsidencementioning
confidence: 99%
“…Westward propagation of peaks in sea level along the southern coast of Japan was found by Shoji (1961) and Isozaki (1969). The propagation occurs in the variations of sea level for periods shorter than 10 days, especially for 4-6 days (Nagano and Kawabe, 2004).…”
Section: Properties Of Propagation Of Coastal Sea Levelsmentioning
confidence: 92%
“…A candidate for the other factors in the third category may be a coastal disturbance propagating westward. Shoji (1961) and Isozaki (1969) reported a westward propagation of sea level along the southern coast of Japan. The propagation occurs in sea level variations for periods shorter than 10 days, especially for 4-6 days (Nagano and Kawabe, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…SHOJI (1961) presumed that this might be a kind of internal Kelvin wave induced by an (41) atmospheric disturbance.…”
Section: Data and Methods Of Analysismentioning
confidence: 99%
“…SHOJI (1961) suggested that this wave might be an internal Kelvin wave induced by a progressive typhoon, but he could not sufficiently verify validity of the assumption because of scantiness of observed data.…”
Section: Introductionmentioning
confidence: 99%